KELAINAN SEKSUAL TOKOH UTAMA PRIA PADA NOVEL KAGI KARYA TANIZAKI JUNICHIRO - Putra, I Gusti Putu Mahendra (Humanis; Volume 9. No. 1. Oktober 2014)
This study entitled "Male Sexual Disorder from the Main Character in Junichiro Tanizaki’s novel, ‘Kagi’". The purpose of this study is to determine the structure of personality and sexual abnormalities experienced by the male main character. This study used descriptive method and informal methods of analysis. The theory used in analyzing is the psychoanalysis theory from Sigmund Freud along with Whitbourne and Halgin’s theory of abnormalities. The results showed that the id element is more commonly found than the other two elements, namely the ego and the superego. The main male characters have desires that demand to be fulfilled. The desire is up to surface in the form of sexual disorder due to the inability of ego and superego to control the id. Sexual disorders experienced by the male main character is voyeurism. Voyeurism is a form of sexual disorder that occurs in a person and that person get sexual satisfaction by the way of peeking.
Keywords: Psychoanalysis, sexual abnormalities, voyeurism.